Control de inventario en insumos de la Farmacia “María Auxiliadora” de la ciudad de Babahoyo periodo 2022. - Herdoiza López, Pedro Ariel (2023)
The present scientific research work entitled "Inventory Control in the "María Auxiliadora" Pharmacy of the City of Babahoyo Period 2022". Study that aimed to establish how inventory control can be adapted to the internal processes of the "María Auxiliadora" pharmacy, located in the city of Babahoyo, during the period 2022-2023. The research was designed as a descriptive study, supported by qualitative research methods, including a bibliographic review on inventory control in pharmacies and its importance in business management. The study used deductive reasoning to create premises based on observations, interviews with the pharmacy owner, and a review of literature resources. Data was collected through observation and interviews, and the study identified a need for an automated inventory management system to improve efficiency, reduce errors, and ensure products are available when needed. The study recommends that the pharmacy establish clear policies and procedures for inventory management and continually monitor inventory levels.